Physicochemical and Nutritional Requirements for Axenic Replication Suggest Physiological Basis for Coxiella burnetii Niche Restriction - Vallejo Esquerra, Eduardo; Yang, Hong; Sanchez, Savannah E.; Omsland, Anders (Frontiers in Cellular and Infection Microbiology, 2017)
Bacterial obligate intracellular parasites are clinically significant animal and human pathogens. Central to the biology of these organisms is their level of adaptation to intracellular replication niches associated with physicochemical and nutritional constraints. While most bacterial pathogens can adapt to a wide range of environments, severe niche restriction—an inability to thrive in diverse environments—is a hallmark of bacterial obligate intracellular parasites. Herein the physicochemical and nutritional factors underlying the physiological basis for niche restriction in the zoonotic bacterial obligate intracellular parasite and Q fever agent Coxiella burnetii are characterized. Additionally, these factors are reviewed in the context of C. burnetii evolution and continued (patho) adaptation. C. burnetii replication was strictly dependent on a combination of moderately acidic pH, reduced oxygen tension, and presence of carbon dioxide. Of macronutrients, amino acids alone support replication under physicochemically favorable conditions. In addition to utilizing gluconeogenic substrates for replication, C. burnetii can also utilize glucose to generate biomass. A mutant with a disruption in the gene pckA, encoding phosphoenolpyruvate carboxykinase (PEPCK), the first committed step in gluconeogenesis, could be complemented chemically by the addition of glucose. Disruption of pckA resulted in a moderate glucose-dependent growth defect during infection of cultured host cells. Although, C. burnetii has the theoretical capacity to synthesize essential core metabolites via glycolysis and gluconeogenesis, amino acid auxotrophy essentially restricts C. burnetii replication to a niche providing ample access to amino acids. Overall, the described combination of physiochemical and nutritional growth requirements are strong indicators for why C. burnetii favors an acidified phagolysosome-derived vacuole in respiring tissue for replication.